2004
DOI: 10.1115/1.1648059
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Reliable Design for a Nonmetallurgical Contact-Joint Structure Consisting of an Adhesive Film

Abstract: The interconnection reliability of a contact-joint structure with anisotropic conductive film (ACF) or non-conductive film (NCF) was evaluated in terms of stability of the compressive force at the contact face between a chip bump and a substrate pad. The key factor that dominates the interconnection reliability during temperature cycling is the amount of plastic strain in the chip bump (gold bump) at the contact face. The plastic deformation of the chip bump must therefore be controlled by selecting the approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Teo et al (2003Teo et al ( , 2005 carried out enhanced moisture sensitivity testing (MST), temperature cycling (TC), high temperature storage (HTS) and pressure cooker testing (PCT) and concluded that the best properties of an ACF for high reliability assemblies included high adhesive strength after being subjected to reliability test conditions, low coefficient of moisture expansion (CME) and low elastic modulus (E). Tanaka et al (2004) investigated the effects of an ACF's material properties and build-up substrate on the interconnection reliability of ACF joints during temperature cycling tests. The results showed that the plastic strain of a bump and pad decreased for ACF joints with an ACF of low CTE and a build-up material with a low Young's modulus, which could improve the interconnection reliability of the ACF joints.…”
Section: Mechanical Characterization Of Bonding Assemblies With Diffementioning
confidence: 99%
“…Teo et al (2003Teo et al ( , 2005 carried out enhanced moisture sensitivity testing (MST), temperature cycling (TC), high temperature storage (HTS) and pressure cooker testing (PCT) and concluded that the best properties of an ACF for high reliability assemblies included high adhesive strength after being subjected to reliability test conditions, low coefficient of moisture expansion (CME) and low elastic modulus (E). Tanaka et al (2004) investigated the effects of an ACF's material properties and build-up substrate on the interconnection reliability of ACF joints during temperature cycling tests. The results showed that the plastic strain of a bump and pad decreased for ACF joints with an ACF of low CTE and a build-up material with a low Young's modulus, which could improve the interconnection reliability of the ACF joints.…”
Section: Mechanical Characterization Of Bonding Assemblies With Diffementioning
confidence: 99%
“…In this structure, the number of I/O pins can be drastically increased because the area-arrayed micro bumps are formed on the whole area of a Si chip surface. However, the complexity of the structure and the difficulty of assembly process must cause low yield of mass production [2]- [5]. Therefore, the reduction of the production cost is indispensable for realizing such 3D-stacked structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this structure, the number of I/O pins can be drastically increased because of area-arrayed micro bumps formed on whole area of Si chip surface. However, the complexity of the structure and the difficulty of assembly process must cause low yield of mass production [2]- [5]. Therefore, the reduction of the production cost is indispensable for realizing such 3Dstacked structures.…”
Section: Introductionmentioning
confidence: 99%